Efektifitas Pembacaan Ratana Sutta oleh Umat Buddha dalam Menghadapi Masa Pandemi Covid 19 - Sukarti Sukarti (Purwadita : Jurnal Agama dan Budaya, 2022)
This study aims to determine the activities of Buddhists at the Dharma Dwipa Temple during the Covid 19 pandemic, the psychological impact and effectiveness of Buddhist reading of the Ratana Sutta in facing the Covid 1 pandemic. The research result show that, Covid 19 pandemic caused limited activities of Buddhists at the Dharma Dwipa Temple, Ponorogo district and the general public. The psychological impact of the spread of the corona virus that is felt is the emergence of fear, anxiety and even panic buying.The quantitative data shows that the effectiveness of the reading of the Ratana Sutta by the Buddhist Dharma Dwipa monastery is very good, this is supported by percentage of 47.3% . Buddhist figures give advice and carry out the recitation of the Ratana Sutta both at the monastery and at home during the devotional service while adhering to health protocols. The reading of the ratana sutta is very effective and precise, because it conditions the mind to be calm and can be a solution to dealing with the psychological impact of the Buddhist Dharma Dwipa Buddhist monastery during the Covid 19 pandemic.  Keywords: The effectiveness, Ratana Sutta, Covid 19 pandemic.